Photodynamic inactivation of planktonic cultures of Streptococcus mutans using erythrosine irradiated by LED - Esper, Maria Ângela Lacerda Rangel [UNESP]; Barbosa, Júnia Oliveira [UNESP]; Alvarenga, Janaína Araújo De [UNESP]; Junqueira, Juliana Campos [UNESP]; Rastelli, Alessandra Nara De Souza [UNESP]; Gonçalves, Sérgio Eduardo De Paiva [UNESP] (Editora Cubo, 2020)
Objective: The aim of this in vitro study was to evaluate the efficacy of photodynamic inactivation (PDI) with erythrosine (E), using a light-emitting diode (LED) on planktonic cultures of Streptococcus mutans. Material and Methods: A Streptococcus mutans strain (UA 159) was used to prepare the suspensions containing 107 cells/mL, which was tested under different experimental conditions: a) LED irradiation in the presence of erythrosine as a photosensitizer (E+L+); b) LED irradiation only (P-L+); c) treatment with erythrosine only (E+L-); and d) no LED irradiation or photosensitizer (P) treatment, which served as a control group (P-L-). After treatment, strains were seeded onto MSBS agar for determination of the number of colony-forming units (CFU/mL). Results: The results were submitted to analysis of variance and the Tukey test (p < 0.05). No reduction in the number of CFU/mL was observed in the treatment group with erythrosine (E+L+) when compared to the control (P-L-). Conclusion: PDI using erythrosine did not reduce the number of CFUs per millimeter within the parameters in this study.
Inativação fotodinâmica de culturas planctônicas de Streptococcus mutans usando eritrosina irradiada por LED
Keywords: Decay; Erythrosine; Light-emitting diode; Photodynamic inactivation